2020
DOI: 10.1590/1983-40632020v5063476
|View full text |Cite
|
Sign up to set email alerts
|

Tomato grafting onto Solanaceae genotypes to control bacterial wilt (Ralstonia solanacearum Smith 1896)

Abstract: The tomato cultivation in the Amazon is not feasible mainly due to the natural infestation of Ralstonia solanacearum in the soil. Preventive control through grafting has been one of the main alternatives to manage this problem. This study aimed to evaluate the compatibility of Solanaceae genotypes as rootstocks for 'Santa Clara' tomato, aiming to control the bacterial wilt. Five rootstocks were evaluated: cubiu; red jurubeba; jurubebão; commercial hybrid tomato rootstock Guardião; and 'Santa Clara' tomato (sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Pereira et al (2018) evaluated 22 accessions and found that 11 were resistant. For other Solanum species evaluated in this study, good compatibility for grafting with tomato was reported in Solanum paniculatum (Pereira et al, 2018), S. crinitum (Carvalho et al, 2020), and S. mammosum (Bletsos & Olympio, 2008), being this first species resistant to M. enterolobii according to Mattos et al (2011), and S. mammosum resistant to M. arenaria (González et al, 2010).…”
Section: Researchmentioning
confidence: 61%
See 1 more Smart Citation
“…Pereira et al (2018) evaluated 22 accessions and found that 11 were resistant. For other Solanum species evaluated in this study, good compatibility for grafting with tomato was reported in Solanum paniculatum (Pereira et al, 2018), S. crinitum (Carvalho et al, 2020), and S. mammosum (Bletsos & Olympio, 2008), being this first species resistant to M. enterolobii according to Mattos et al (2011), and S. mammosum resistant to M. arenaria (González et al, 2010).…”
Section: Researchmentioning
confidence: 61%
“…Solanum crinitum has also presented six among seven accessions with resistant response. This species is used in Brazil as a tomato rootstock to control bacterial wilt (Carvalho et al, 2020), but there was no information available about its resistance to M.…”
Section: Resultsmentioning
confidence: 99%